EXAMINATION OF CHEMICAL VARIATIONS IN FOSSIL RESIN WITH TWO-PHOTON EXCITATION FLUORESCENCE AND PALEOBOTANICAL INVENTORY REPORTS ON NATIONAL PARK SERVICE UNITS - (:unkn) unknown (My University, 2024)
Fossil resin can be difficult to chemically characterize due to its complex chemistry which can be complicated by a unique chemistry for each fossil resin sample. Using two-photon excitation fluorescence micro-spectroscopy, we measured the wavelengths at peak emission intensity: we compared these fluorescence results to FTIR spectra. There are variations in fluorescence which indicate differences in botanic origin. This method may be used in future research to better understand botanic origin when more traditional analyses fail.There has been a need for a comprehensive paleobotanical inventory report for NPS units. Four teams consisting of graduate students and mentors are completing the reports. There will be reports based on paleobotanical resources found in different eras within NPS units. With the paleobotanical inventory reports, we can better demonstrate the significance of paleoflora at NPS units as well as the management issues which may impact the preservation and research of these plant fossils.
Keywords: amber; fluorescence; fossil resin; National Park Service; paleobotany; two-photon excitation